Determination of some trace elements in various lichens as biomonitors of pollution and assessment of pollution status - Topal, Murat; Topal, E.ışıl Arslan; Öbek, Erdal; Aslan, Ali (My University, 2023)
Some trace elements in various lichens as biomonitors of pollution were investigated. Also, the pollution status was assessed by enrichment factor, contamination factor, and pollution load index. Investigated elements were Ta, Bi, Hf, Nb, Ga, Sc, Li, Y, Ce, and Sr. The lichen species were Rhizoplaca chrysoleuca, Umbilicaria vellea, Aspicilia calcarea, Pseudevernia furfuracea, and Cetraria islandica. According to the results, lichen species accumulate Sr element well. The highest trace element accumulated by Pseudevernia furfuracea (21.7±1.0 mg/kg; 75%), Rhizoplaca chrysoleuca (31.9±1.6 mg/kg; 61%), Umbilicaria vellea (16.3±0.8 mg/kg; 59%), Aspicilia calcarea (77.9±3.8 mg/kg; 88%), and Cetraria islandica (22.7±1.1 mg/kg; 75%) was determined as Sr. The highest CFs in lichens investigated were calculated for Sr, Ta, and Li. PLI values for Cetraria islandica, Aspicilia calcarea, and Umbilicaria vellea were greater than 1. As a result, it has been proven that these lichen species can be used as good biomonitors of pollution.
Keywords: Pollution; biomonitor; Accumulation; lichen